Les villes des Habsbourg du XVe au XIXe siècle Communication, art et pouvoir dans les réseaux urbains - Pelizaeus, Ludolf (Studia Habsburgica, 2021)
What is 'typically' habsburgish about the network of cities that were under the rule of the imperial dynasty for several centuries? As a place of artistic and intellectual production, as an economic hub, as a decision-making centre, the limited space of the city interacted with the empire. The contributions brought together in this book study the influences and exchanges (economic relations, political culture, artistic productions) that shaped the territories governed by the Habsburgs in Spain, Italy, the Netherlands, Hungary, Austria and America, from the modern era to the contemporary period. The traces of these interactions testify of the unique role played by urban cooperation in the development of a composite monarchy.